Gareth C. Sampson (2019), Rome, Blood & Power. Reform, Murder and Popular Politics in the Late Republic 70-27 BC. Reino Unido: Sword & Pen. 338 págs. - Ortiz Delgado, Francisco Miguel (Revista de Historia Universal, 2022)
There are topics that never cease to be attractive to the general academic and intellectual world, at least in “western culture”. Two of those topics that will continue to be studied without the enthusiasm for them diminishing are: 1) the political-military career of Gaius Julius Caesar, and 2) the theme of the fall of the republican regime in ancient Rome.